Patterns of chronic hand eczema: a semantic map analysis of the CARPE registry data. (1st January 2018) - Cazzaniga, S.; Apfelbacher, C.; Diepgen, T.; Ofenloch, R.F.; Weisshaar, E.; Molin, S.; Bauer, A.; Mahler, V.; Elsner, P.; Schmitt, J.; Ballmer‐Weber, B.K.; Spring, P.; et al.
Summary: Background: Hand eczema has a high incidence and prevalence and has a negative impact on both physical and psychological well‐being, with the risk of persistence as a chronic condition. Epidemiological studies on hand eczema provided mainly descriptive and risk analyses, but pattern analyses of variables associated with hand eczema, in particular chronic hand eczema, have not been explored to date. Objectives: To investigate and display the semantics of associations between variables of hand eczema obtained from the Swiss and German registries of chronic hand eczema (CARPE) to dissect patterns and novel links. Methods: This was a cross‐sectional study on selected variables from the CARPE registries. Associations between variables were analysed by means of an autoassociative system. A semantic connectivity map was generated by using a maximum spanning tree algorithm. Results: Baseline datasets of 1466 patients with chronic hand eczema (Switzerland: 199; Germany: 1267) were analysed. Occupational exposure had the highest impact in the total and country cohorts. We identified two areas of exposure linked to corresponding occupations that clearly demarcated the sexes. Conclusions: This study, using semantic connectivity as a novel method of data analysis, reveals the complexity of features characterizing chronic hand eczema as well as novel association patterns that deserve further investigation.